GRANUL MINYAK SERAI DAPUR SEBAGAI LARVASIDA NYAMUK Aedes aegypti - Sri Mulyani (Faculty of Pharmacy, Universitas Gadjah Mada, 2014)
One way to prevent the spread of Haemorrhage Dengue Fever is the use of abate. The use of abate as larvicides often complained causing an unpleasant smell, and can cause resistance. Lemongrass oil is reported to have activity as larvicides, and this study aims to make granules of lemongrass oil preparation, as well as determining the value of LC50, LC90 against larvae of Ae. aegypti instar III. The granules of lemongrass oil preparation are made with lactose filler and binder CMC-Na. Larvicidal activity test using 20 larvae, 5 concentration solution to each granules, and contacted for 24 hours. Measurement of total larvae deaths, and data were analyzed using probit analysis from Finney modification, to determine the LC50 and LC90 values. Results shown that lemongrass oil can be made as granules with lactose filler and CMC-NA binder. The LC50 and LC90 values of granules from lemongrass oil are 38,30ppm and 51,57ppm.